Gender Inequality of Women in the Film Sehidup Semati by Upi Avianto: A Theoretical Study by Mansour Fakih - Retno Dwi Ayuningrum; Abdul Aziz Khoiri (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the forms of subordination, stereotypes, and violence experienced by female characters in the film “Sehidup Semati” and explain how the relationship between the narrative in the film “Sehidup Semati” with social reality related to the position of women in society. This research was conducted on the film “Sehidup Semati” by Upi Avianto which was released in 2024. The population in this study are scenes, dialogues, and narratives in the film “Sehidup Semati”, while the sample in this study is scenes, dialogues, and narratives that represent gender inequality experienced by female characters in the film “Sehidup Semati”. The research instrument in this study is the researcher himself who watched, understood, and analyzed the film “Sehidup Semati”. The data collection technique in this study uses documentation techniques. The data analysis tool in this study is using the theory of gender inequality by Mansour Fakih who views gender inequality as arising from society’s mistaken perspective regarding the concept of gender itself. The results of the study found six forms of gender inequality experienced by the female character Renata in the film “Sehidup Semati” namely subordination, stereotypes, and violence. This includes two data on subordination, two data on stereotypes, and two data on violence.